PIC simulation for W-band planar helix with straight-edge connections - Chua, Ciersiang (2013)
A square cross section planar helix with straightedge connections has been simulated with a cylindrical electron beam for traveling-wave tube amplifier application. The saturated output peak power varies from 0.65 W to 2.58 W over the frequency range of 85-110 GHz. The maximum electronic efficiency is 7.3% at 97.5 GHz for a beam of 5.8 kV and 8 mA.